Personnel adjustments during the Covid-19 pandemic: Did co-determination make a difference? - Daniel Fackler; Claus Schnabel; Jens Stegmaier (Journal for Labour Market Research, 2024)
Using a unique dataset of establishments in Germany surveyed during the Covid-19 pandemic, this study investigates whether personnel adjustments during the crisis differed between establishments with and without a works council. Our regression analyses show that the hiring and dismissal rate as well as the churning rate were lower in establishments with a works council. In contrast, the net employment growth rate over the pandemic and the implementation of short-time work did not differ significantly between establishments with and without a works council. We conclude that worker co-determination did indeed make a difference in terms of higher employment stability for the incumbent workforce during the pandemic.
Keywords: M51; J53; J63; 330; Covid-19 pandemic; Co-determination; Personnel adjustments; Works councils